Early Functional Outcome: Comparison Between Bipolar and Unipolar Hemiarthroplasty (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To compare Bipolar and unipolar hemiarthoplasty (HA) treatment for neck of femur fracture in elderly population.Methods: This is a descriptive randomized study, conducted from January 2014 to May 2015. All the patients were sixty years and above with Garden type III and IV Neck of femur fracture. The patients were randomly placed in two groups. Group A were treated with bipolar and B with unipolar Austin Moor (AM) hemiarthoplasty (HA). Non-weight bearing mobilization on 1st postoperative day. Weight bearing with crutches on 3-5th postoperative day. Early outcome was assessed at 3 months follow-up, using Harris hip score.Results: Thirty patients were divided into two groups, i.e., 15 in each. Patients in group A have returned to daily living activities earlier then patients in group B. Group A has 87% (n=13) excellent, 13% good with no fair and poor results while group B has 53% excellent, 33% good and 13% fair results.Conclusion: Bipolar hemiarthoplasty is an effective treatment for neck of femur fractures in elderly population.